Analisis Pengaruh Representasi Visual pada Dasbor dan Implementasi Formulir Sebagai Solusi - Jovian, Ernestito; Trisnawarman, Dedi; Perdana, Novario Jaya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
This study analyzes the effectiveness of visual representations on dasbors as a tool to increase employee understanding. By focusing on companies that have a variety of complex information, this study evaluates the various types of visual representations used in dasbors and their impact on employee understanding. Through comprehensive analytical methods, including survey and observation data collection, this study identified the strengths and limitations of each type of visualization implemented. The results provide valuable insights into which visual representation strategies are most effective in communicating information to employees, thereby guiding improvements to dasbor designs that are more responsive and informativeKeywords: Dasbor; visualization; EffectiveÂ AbstrakPenelitian ini menganalisis efektivitas representasi visual dalam dasbor sebagai alat untuk meningkatkan pemahaman karyawan dalam pentingnya representasi visual dalam kegunaan dasbor. Dengan fokus pada perusahaan yang memiliki beragam informasi yang kompleks, penelitian ini mengevaluasi berbagai jenis representasi visual yang digunakan dalam dasbor dan dampaknya terhadap pemahaman karyawan. Melalui metode analisis komprehensif, termasuk pengumpulan data survei dan observasi, penelitian ini mengidentifikasi kekuatan dan keterbatasan dari setiap tipe visualisasi yang diimplementasikanÂ